1979
DOI: 10.1016/0035-9203(79)90092-0
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei: miniature anion-exchange centrifugation technique for detection of low parasitaemias: adaptation for field use

Abstract: The miniature anion-exchange/centrifugation (AEC) method, originally developed for the detection of submicroscopic trypanosomaemias in laboratory rodents, has been adapted for the diagnosis of trypanosomiasis in man in the field using blood samples obtained by finger-prick. It has been tested in a survey in The Gambia. The method is shown to be highly sensitive and to fulfil the first essential criteria for exploitation in the field, namely, that it can be operated in the open air under tropical conditions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(77 citation statements)
references
References 7 publications
0
71
0
6
Order By: Relevance
“…CATT whole blood seropositives were tested subsequently in CATT on plasma (Magnus et al, 1978). Parasitological tests (mAECT which is the mini anion exchange column technique Lumsden et al, 1979, and direct examination of lymph node aspirate) were only performed on the subjects positive to CATT on plasma or harbouring adenopathies.…”
Section: Sleeping Sickness Surveymentioning
confidence: 99%
“…CATT whole blood seropositives were tested subsequently in CATT on plasma (Magnus et al, 1978). Parasitological tests (mAECT which is the mini anion exchange column technique Lumsden et al, 1979, and direct examination of lymph node aspirate) were only performed on the subjects positive to CATT on plasma or harbouring adenopathies.…”
Section: Sleeping Sickness Surveymentioning
confidence: 99%
“…Direct detection of trypanosomes in host blood was performed by using the miniature anion exchange centrifugation technique (m-AECT) (Lumsden et al 1979;Mehlitz 1986). In brief, z ml polypropylene syringes were filled with DEAE-cellulose (type DE52; Whatman, Maidstone, UK) pre-swollen in phosphate buffered saline (PBS) pH 8.2.…”
Section: Direct Detection Of Trypanosomesmentioning
confidence: 99%
“…[12], in blood samples obtained at 1, 2, 4, 7, 14 and 29-34 days after pen-tamidine administration, showed that only three patients (2, 3 and 10) had uniformly detectable concentrations. The plasma phenobarbitone concentrations varied between 20 and 86 gmol l-1, except in patient 10 whose levels were in the range [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] ,umol 1-1 (the therapeutic range for treatment of convulsive disorders is 40-135 gmol l-l). A majority of the subjects were also given a single intramuscular injection of betamethasone (Diprostene®, ScheringPlough, Levallois-Perret, France).…”
Section: Concomitant Medicationmentioning
confidence: 99%